2009
DOI: 10.2217/fmb.09.88
|View full text |Cite
|
Sign up to set email alerts
|

Protein Glycosylation in Candida

Abstract: Candidiasis is a significant cause of invasive human mycosis with associated mortality rates that are equivalent to, or worse than, those cited for most cases of bacterial septicemia. As a result, considerable efforts are being made to understand how the fungus invades host cells and to identify new targets for fungal chemotherapy. This has led to an increasing interest in Candida glycobiology, with an emphasis on the identification of enzymes essential for glycoprotein and adhesion metabolism, and the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 178 publications
(153 reference statements)
1
78
0
Order By: Relevance
“…11), where an oligosaccharide is covalently attached to Asn and Thr/ Ser residues, respectively, and the addition of GPI at the C terminus, which is known as a GPI anchor (548)(549)(550). These biosynthetic pathways are essential for cell viability, to maintain proper cell wall structure and organization, and for virulence (549)(550)(551).…”
Section: Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…11), where an oligosaccharide is covalently attached to Asn and Thr/ Ser residues, respectively, and the addition of GPI at the C terminus, which is known as a GPI anchor (548)(549)(550). These biosynthetic pathways are essential for cell viability, to maintain proper cell wall structure and organization, and for virulence (549)(550)(551).…”
Section: Glycosylationmentioning
confidence: 99%
“…The ER ␣-glycosidases participating in the N-linked glycosylation pathway also have a role in glycoprotein endoplasmic reticulum-associated degradation, where misfolded proteins are labeled for degradation by the cytosolic proteasome (572). Once transferred to the protein backbone and processed by glucosidase I, the Glc 2 Man 9 GlcNAc 2 oligosaccharide is trimmed by glucosidase II, generating GlcMan 9 GlcNAc 2 (550). This monoglucosylated oligosaccharide is recognized by calnexin and calreticulin, which in turn interact with ERp57/Pdi1, facilitating protein folding (572).…”
Section: Glycosylationmentioning
confidence: 99%
“…They are very hetero geneous in nature and are either present as a peptidomannan in yeast or as part of the constructive polysaccharides of the cell wall, such as the galactomannan in A. fumigatus [21]. [22]. However, deletion of these mannosyltransferases is not essential in yeast.…”
Section: Identifying New Targets and Revisiting Old Targetsmentioning
confidence: 99%
“…They are postulated to act as modulators of properties of cellular membranes since studies on model membranes have shown that polyisoprenoids increase membrane fluidity and permeability [8][9][10]. On the other hand, the role of phosphorylated dolichols as cofactors in protein glycosylation and glycosylphosphoinositol (GPI) anchor synthesis in eukaryotic cells is well characterized [11][12][13]. Recently, a new function for dolichols and polyprenols has been proposed -as a shield against reactive oxygen species (ROS) [14].…”
Section: Introductionmentioning
confidence: 99%